A DESIGN MODEL AND COMPARISON OF FIXED AND TRACKING PHOTOVOLTAIC SYSTEMS FOR A SINGLE-FAMILY HOUSE IN ERBIL, IRAQ - ABDULLAH, HARDI K.; ABDULKARIM, PARINAZ M. (Journal of Duhok University, 2023)
Solar power through the use of photovoltaic (PV) system is the most advanced and profitable renewable energy application; however, there are still a number of obstacles facing this technology, including technical, financial, and political barriers. According to meteorological data of Iraq, the annual average solar radiation is about 1800-2390 kWh/m2/year, which is a considerable amount of energy if properly utilized. This study proposes a design model of PV installation system and the model is applied to three different PV systems for installation in a residential household in Erbil, Iraq. The study examines the feasibility of the plants proposed and compares the efficiency of both fixed and tracking PV systems for an off-grid PV system. The PVsyst software is used for household electricity load estimation and solar energy requirements, such as the appropriate number of panels, maximizing AC power generation, the storage capacity of the battery, and charge controller size to fulfill the required load. To calculate the annual energy generation, the design data was used in the simulations. Three scenarios were simulated; fixed panels, East-West single tracking, and dual-axis tracking systems based on the altitude and azimuth tracking angles. The study compared both the photovoltaic properties and the amount of energy generated by the installed systems. The results showed that the dual-axis tracking system is 30% and single-axis tracking system is 21% more efficient than the fixed PV system, although the latter offers an economically better alternative.